An analysis of media competence from the Peruvian cinematographic violence - Hartley-Menini, Chiara; Rolleri-García, Jair-Augusto; Gallardo-Echenique, Eliana (Cuadernos de Documentación Multimedia, 2021)
The overrepresentation of cinematographic violence and the incipient formation of media skills in Peru invite one to wonder how the Peruvian audience analyzes violent films. This article addresses media competence qualitatively and from the dimension of ideology and values. Six focus groups were conducted with men and women of different ages, based on violent scenes from two Peruvian films. The results show that there is a development of competencies within the dimension studied. However, these capacities converge with forms of naturalization of violence, relativization of its effects and certain gaps in the ethical judgment that grounds its consumption. The research contributes to an understanding of the factors and nuances that surround the critical capacities of the audience, beyond self-perception and mastery of technologies. At the same time, it opens debates on the relationship between cinema and violence from the subjectivity and critical judgment of the spectator.